Laser yelken sporcularında pençe kuvveti ile iskota halatı çekme kuvveti ilişkisinin değerlendirilmesi - Tuncel, Sevgi (My University, 2023)
Tezin başlığı: Laser Yelken Sporcularında Pençe Kuvveti ile İskota Halatı Çekme Kuvveti İlişkisinin Değerlendirilmesi Amaç: Bu araştırmada laser sınıfı yelken sporcularının el kavrama kuvveti ile iskota halatı çekme kuvveti arasındaki ilişkinin ve dayanıklılık değerlerinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Araştırmaya; 16 yaş ve üzeri, (yaş; 17,65±1,62 yıl, boy; 176±5,59 cm, vücut ağırlığı; 76,5±6,45 kg, beden kütle indeksi; 23,80±1,76 kg/ m2) lisanslı, en az 4 yıl spor geçmişi olan, sağlıklı, 17 laser sınıfı yelken sporcusu gönüllü katıldı. Sporculara laser trapez antrenman aleti üzerinde el kavrama kuvvet testi ve iskota halatı çekme kuvvet testleri yapıldı. El kavrama kuvvetinin tespit edilmesinde kuvvet ölçme sensörü ve iskota halatı çekme kuvvet tespitinde loadcell (model DYLY-107) ve Sensör Platform V1.0 yazılımı kullanıldı. Bulgular: Araştırmaya katılan laser sınıfı yelken sporcularının el kavrama kuvveti ve iskota halatı çekme kuvveti değerlerine incelendiğinde kuvvetler arasında ilişki olmadığı (p>0,05), sağ ve sol el kuvvet değerleri arasında iki el arasında pozitif yönde ilişki olduğu bulundu (p<0,01). Dayanıklık verileri incelendiğinde el kavrama ve çekme kuvveti arasında (p<0,05) ve sağ ile sol el kavrama ve iskota halatı çekme dayanıklılık değerleri arasında anlamlı fark bulundu (p=0,046). Sonuç: Sporcuların el kavrama kuvveti ve iskota halatı çekme kuvvetinde, sağ ve sol el kuvvetlerinin birbiri ile pozitif yönde ilişkisi olduğu görüldü. Dayanıklılık değerlerine göre el kavrama ve iskota halatı çekme kuvveti arasında ve sağ ile sol el kuvvetleri arasında anlamlı fark bulundu. Dayanıklılık, kavrama kuvveti, laser yelken, maksimal kuvvet, trapez

Title of Thesis: Evaluation of the Relationship between Hand Grip Strength and Pulling Strength of the Sheet Rope in Laser Sailing Athletes Objective: In this study, it was aimed to examine the relationship between the hand grip strength and the pulling strength of the sheet rope and the endurance values of laser class sailing athletes. Materials and Methods: In the study, 16 years and older, (age; 17,65±1,62 years, height; 176±5,59 cm, body weight; 76,5±6,45 kg, body mass index; 23,80 ±1,76 kg/ m2) licensed, healthy, 17 laser class sailing athletes with at least 4 years of sports history participated voluntarily. Hand grip tests and sheet rope pull tests were performed on the laser hiking training device. To determine the hand grip and the pulling strength of the sheet rope, the loadcell (model DYLY-107) and Strength Sensor Platform V1.0 software were used. Results: Evaluating the pulling strength values of the hand grip and sheet rope pulling of the laser class sailing athletes participating in the research, it was found that there was no relationship between the hand grip and the pulling strength values of the sheet rope (p>0,05). When the pulling strength values of the right and left hand grip and sheet rope were examined, it was found that there was a positive correlation between the two hands (p<0,01). When the endurance data were examined, a significant difference was found between hand grip and pulling strength (p<0,05), and between right and left hand grip and pull strength values (p=0,046). Conclusion: It was observed that the right and left hand strengths were correlated with each other and had a positive effect on the grip strength and sheet rope pull strength of the athletes. There was a significant difference between the strength of the hand grip and pulling strength of the sheet rope and the strengths of the right and left hand according to the endurance values. Endurance, hand grip, laser sailing, maximal strength, hiking
Evaluation of the relationship between hand grip strength and pulling strength of the sheet rope in laser sailing athletes
Keywords: Athletes; Dayanıklılık; Hand grip; Hiking; Kavrama kuvveti; Laser sailing; Laser yelken; Maksimal kuvvet; Maximal strength; Sailing; Spor; Sporcular; Sports; Trapez Endurance; Yelkencilik